1970
DOI: 10.1055/s-0038-1654267
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Studies in 45 Cases of Nephrotic Syndrome without Uremia

Abstract: SummaryCoagulation studies were performed in 45 cases of nephrotic syndrome without uremia. The most striking features were an increase in the number of thrombocytes, and in the level of fibrinogen, factor V and factor VIII. Thrombin time was usually prolonged and the titre of antithrombin III was increased. No fibrin breakdown products were found in the serum. 13 patients developed thrombotic complications, with eventual death in 5 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 3 publications
(3 reference statements)
5
86
2
Order By: Relevance
“…Fbg is one of these factors, and the increase of this factor was thought to be induced as a nonspecific hepatic response to heavy proteinuria (Takeda 1967). In agreement with the previous reports (Kanfer et al 1970), the majority of our patients showed increased levels of Fbg and proteinuria with hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Fbg is one of these factors, and the increase of this factor was thought to be induced as a nonspecific hepatic response to heavy proteinuria (Takeda 1967). In agreement with the previous reports (Kanfer et al 1970), the majority of our patients showed increased levels of Fbg and proteinuria with hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 94%
“…It has been stated that nephrotic syndrome is often associated with hypercoagulability (Kanfer et al 1970 ;Kendall et al 1971;Thomson et al 1974). The cause is, however, still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…There is a @@Table1. Systemic Thrombolism in Nephrotic Syndrome @@NephroticSyndrome and Anticoagulant Therapy correlation between increases in Factor V and Factor VIII, and a fall in serum albumin (7). An increase in these coagulation factors might contribute to the high incidence of thromboembolism in nephrotic syndrome.…”
Section: Systemic Thromboembolismmentioning
confidence: 99%
“…[1][2][3] Although the association between nephrotic syndrome and thromboembolic complications has been recognized for more than a century, the precise causal relationship is not entirely understood. [4][5][6] Moreover, the association between the increased bleeding tendency and nephrotic syndrome is also somewhat unclear. [2][3][4][5][6][7] In this review, we present a current synopsis on the subject and discuss some of the controversial aspects that have emerged during the past decade.…”
mentioning
confidence: 99%
“…[4][5][6] Moreover, the association between the increased bleeding tendency and nephrotic syndrome is also somewhat unclear. [2][3][4][5][6][7] In this review, we present a current synopsis on the subject and discuss some of the controversial aspects that have emerged during the past decade. 8,9 An in-depth understanding of the underlying pathogenesis should pave the way to better clinical methods for preventing these grave complications.…”
mentioning
confidence: 99%